2014
DOI: 10.1590/s0100-736x2014001200011
|View full text |Cite
|
Sign up to set email alerts
|

Doenças de asininos e muares no semiárido brasileiro

Abstract: As doenças de asininos e muares na região semiárida do nordeste do Brasil foram avaliadas em um estudo retrospectivo dos 258 atendimentos realizados no Hospital Veterinário da Universidade Federal de Campina Grande no período de janeiro de 2002 a dezembro de 2012. Dos prontuários desses animais foram coletados dados referentes a identificação, anamnese, exame clínico, diagnóstico, protocolo de tratamento e evolução dos casos. Durante o período analisado foram atendidos 200 asininos e 58 muares. Os sistemas afe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
9
0
3
Order By: Relevance
“…Datos similares fueron registrados por Pessoa y colaboradores (20), quienes encontraron miasis (2,9 %), abscesos (13,2 %), dermatofilosis (1,5 %), papilomatosis (1,5 %) y fotosensibilización (1,5 %). Posteriormente, los mismos autores registraron miasis (0,8 %), abscesos (3,5 %), dermatofitosis (1,6 %) y dermatofilosis (0,4 %) en burros del semiárido brasilero (21). Por otra parte, Assis-Brasil y colaboradores (11) y Marcolongo-Pereira y colaboradores (24) encontraron frecuencias de melanoma del 1,2 y 3 % y de papiloma del 4,7 y 6,6 % de los casos en caballos de la región sur de Río Grande del Sur, respectivamente.…”
Section: Discussionunclassified
“…Datos similares fueron registrados por Pessoa y colaboradores (20), quienes encontraron miasis (2,9 %), abscesos (13,2 %), dermatofilosis (1,5 %), papilomatosis (1,5 %) y fotosensibilización (1,5 %). Posteriormente, los mismos autores registraron miasis (0,8 %), abscesos (3,5 %), dermatofitosis (1,6 %) y dermatofilosis (0,4 %) en burros del semiárido brasilero (21). Por otra parte, Assis-Brasil y colaboradores (11) y Marcolongo-Pereira y colaboradores (24) encontraron frecuencias de melanoma del 1,2 y 3 % y de papiloma del 4,7 y 6,6 % de los casos en caballos de la región sur de Río Grande del Sur, respectivamente.…”
Section: Discussionunclassified
“…In Brazil, only some studies approach the main equine diseases [ 17 , 22 , 23 ]. However, the literature is limited regarding equine diseases, with only two studies [ 11 , 12 ] conducted in the Brazilian semiarid region being found.…”
Section: Relationship Between Disease Occurrence and Type Of Donkementioning
confidence: 99%
“…Regarding skin diseases in productive animals, the literature lacks studies on dermatopathies and their risk factors, especially in Brazil. Until recently, retrospective studies in ruminants and equids [ 9 , 10 ] have been highlighted in the country, whereas studies on donkeys are still incipient [ 11 , 12 ]. In this context, the objective of this study was to present a literature review on skin diseases in donkeys and mules.…”
Section: Introductionmentioning
confidence: 99%
“…It irrigates the brain, neck and head and originates the internal carotid, external carotid and occipital arteries, besides several collateral branches, among them the muscular, tracheal and esophageal branches and also the cranial and caudal thyroid, ascending pharyngeal and parotid arteries (Getty 1981, Khamas et al 2002, Ozgel et al 2004, Krupinski et al 2006. The diseases of the central nervous system (CNS) in equines and mules are a relatively important part of those treated by the veterinarian (Pessoa et al 2014, Aguiar et al 2014, Aguiar 2015.…”
Section: Introductionmentioning
confidence: 99%